Fixed Target Program at the LHC - Di Nezza, P.; Carassiti, V.; Ciullo, G.; Engels, R.; Lenisa, P.; Pappalardo, L. L.; Santimaria, M.; Steffens, Erhard; Tagliente, G. (Proceedings of Science, 2024)
Collisions provided by a TeV-scale beam at the LHC on a fixed target will explore a unique kinematic region that has been poorly probed until now. Furthermore, advanced detectors make available probes that have never been accessed before. The LHCb spectrometer possesses the unique capability to function as a fixed-target experiment by injecting gas into the LHC beampipe while proton or ion beams are circulating. The resulting beam-gas collisions cover an unexplored energy range above that of previous fixed-target experiments but below the energies of the RHIC or LHC collider. In light of this, the LHCspin project aims to develop innovative solutions and cutting-edge technologies to access the field of spin physics over the next few years. This will be achieved by exploring a unique kinematic regime and exploiting new reaction processes. To accomplish this goal, a polarized gaseous target will be operated in combination with the high-energy, high-intensity LHC beams and the highly performing LHCb particle detector. This configuration has the potential to open new physics frontiers and deepen our understanding of the intricacies of strong interaction in the non-perturbative regime of QCD. With center-of-mass energies per nucleon up to 115 GeV and utilizing both proton and heavy-ion beams, this setup covers a wide backward rapidity region, including the poorly explored high Bjorken-x and high Feynman-x regimes. This ambitious task is based on the recent installation of an unpolarized gas target (SMOG2) in the LHCb spectrometer. This setup not only constitutes a unique project but also provides an invaluable platform for its polarized upgrade. This article offers an overview of the physics potential, a description of the LHCspin experimental setup, and details the initial findings from the SMOG2 system.
CRIS-Team Scopus Importer:2025-02-04